Fabrication and characterization of electrospun zein-based scaffolds for soft tissue engineering - Massone, Agustina (2017)
Nanofibers and nanomaterials are potentially recent additions to materials in relation to tissue engineering (TE). TE involves the regeneration of biological tissues, which are damaged, using cells with the aid of supporting structures and biomolecules. Mimicking the architecture and functions of extracellular matrix is one of the challenges for TE. Conventional treatments, such as transplantations and the use of mechanical assist devices, could be replaced with this approach. Electrospinning is a versatile and simple technique to produce polymer fibers with diameters varying from 5 nm to 5 μm, which can mimic the extracellular matrix. This characteristic stimulates the expression of specific signals and, in combination with growth factors and proteins, has an important influence in cellular activity. Blending synthetic with natural polymers, combine the advantages of both leading to good biodegradation and mechanical properties, and excellent cell adhesion and growth. In this work, it is presented the preparation and characterization of natural polymer (zein)-based nanofibrous scaffolds obtained through electrospinning technique. The processing parameters were adjusted to obtain randomly-oriented nanofibrous mats. Although the basic principles of the technique are simple, the many factors and parameters involved in it make the process complex. Through the analysis of testing results, it was found that the blend of zein with synthetic polymers improve in many folds its properties. The nanofibrous mats are of great interest for its applications in tissue engineering.